Correlation of raised serum uric acid in first trimester of pregnancy and the risk of gestational diabetes: a prospective study - Mohan, Jayanthi; Suriyamoorthi, Janani; Menon, Maya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prevalence of Gestational Diabetes Mellitus (GDM) is fast increasing in India. The association between serum uric acid levels and GDM is not well known. This study was conducted to assess the relationship between first trimester serum uric acid levels and the incidence of gestational diabetes. Methods: This prospective observational study included 85 antenatal women. Serum uric acid level and oral glucose challenge test (OGCT) were done in all three trimesters. Women with first trimester serum uric acid levels of <3.6 mg were classified as group A and >3.6 mg as group B. Both the groups were followed throughout the pregnancy to assess the development of gestational diabetes. Also, the mode of delivery, pregnancy outcome, and other maternal and neonatal complications were observed. Results: In the patients recruited into this study, 33.33% of group A (serum uric acid<3.6 mg/dl) and 17.5% of group B (serum uric acid>3.6 mg/dl) developed GDM. Conclusions: First trimester Serum Uric acid was not significantly related to development of GDM in the sampled women. Neither was it related to any adverse maternal or fetal outcomes.